Analisis Kelayan Usahatani Belimbing (Averhoa Carambola) Di Desa Tempuran Kecamatan Demak Kabupaten Demak - Umul Anisatul Rohmah; Sri Wahyuningsih; Hilmi Ariji Fachriyan (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Analysis of Honey Starfruit Farming in Tempuran Village provides an overview of the economic contribution of this sector to the region. This study aims to analyze the costs, revenues, income, BEP and R / C of Starfruit honey business in Tempuran Village, Demak District, Demak Regency. The method used in this study uses a descriptive method. This study was conducted in the last post-harvest period of October-November 2024. The number of farmers involved in this study was 40 Honey Starfruit farmers. The results showed an average total cost of Rp. 5,184,832 / harvest / 0.7 Ha on private land, an average production amount of 1312.5 Kg / harvest season / 0.7 Ha and an average selling price of Rp. 10,000 / Kg, resulting in an average total income of Rp. 13,125,000 / harvest season / 0.7 Ha, resulting in an average income of Rp. 7,940,168/ 0.7 Ha / harvest season. The average calculation of BEP production is 518.4/Kg/0.7Ha/harvest season and BEP price is Rp 4,071/0.7Ha/harvest season. Therefore, the average RC ratio value of water apple farming is 2.58. Keywords: honey starfruit , Cost, Income, Revenue, BEP, R/C